Learning across the UK: a review of public health systems and policy approaches to early child development since political devolution. (5th March 2019) - Black, Michelle; Barnes, Amy; Baxter, Susan; Beynon, Claire; Clowes, Mark; Dallat, Mary; Davies, Alisha R; Furber, Andrew; Goyder, Elizabeth; Jeffery, Catherine; Kritsotakis, Evangelos I; Strong, Mark
Abstract: Background: Giving children the best start in life is critical for their future health and wellbeing. Political devolution in the UK provides a natural experiment to explore how public health systems contribute to children's early developmental outcomes across four countries. Method: A systematic literature review and input from a stakeholder group was used to develop a public health systems framework. This framework then informed analysis of public health policy approaches to early child development. Results: A total of 118 studies met the inclusion criteria. All national policies championed a 'prevention approach' to early child development. Political factors shaped divergence, with variation in national conceptualizations of child development ('preparing for life' versus 'preparing for school') and pre-school provision ('universal entitlement' or 'earned benefit'). Poverty and resourcing were identified as key system factors that influenced outcomes. Scotland and Wales have enacted distinctive legislation focusing on wider determinants. However, this is limited by the extent of devolved powers. Conclusion: The systems framework clarifies policy complexity relating to early child development. The divergence of child development policies in the four countries and, particularly, the explicit recognition in Scottish and Welsh policy of wider determinants, creates scope for this topic to be a tracer area to compare UK public health systems longer term.